Study of correlations between selection traits of oat genotypes in Akmola region - Dyussibayeva, Elmira; Dolinny, Y.; Zhirnova, I.; Rysbekova, A.; Zeinullina, A.; Orazov, A.; Izbastina, K.; Abylkairova, M. (Fundamental and Experimental Biology, 2025)
The research aimed to study the correlations between the valuable agronomic traits of oat (Avena sativa), which are necessary in plant selection programs to increase productivity. The study was conducted in 2023-2024 in the field experimental plots of A.I. Barayev Research and Production Centre for Grain Farming; the observations were carried out using biometric measurements of plant height and morphological features of plant productivity. Biological material consisted of 16 oat genotypes; experimental data were collected from all genotypes. The results were interpreted by determining the correlation coefficients, analysing the variance of multiple regression, and studying the relationship between the traits. The study shows that productive tillering is in a linear relationship with the other characteristics, except for the weight and number of grains in a panicle (r=-0.39-0.46). According to the results of correlation analysis, the following pairs of the related traits were determined: weight of 1000 grains and plant height, seed weight per plant and panicle length (r=0,38-0,46), productive tillering and seeds weight per panicle (r=0,46); that can be effectively used to achieve high yield in selection process. According to the results of structural analysis of productive elements, the genotypes featuring a complex of valuable traits were selected: Yarovoy and Fax varieties, as well as the FL 0524 sample. These valuable genotypes can be recommended as sources for increasing productive properties in oat plants